Non-inferiority studies with multiple reference treatment - HUANG, Li-Ching (Institutional Knowledge at Singapore Management University, 2015)
The increasing popularity of noninferiority trials reflects the ongoing efforts to replace existing treatments (reference treatments) with new treatments (experimental treatments) that retain a substantial fraction of the effect of the reference treatments. The adoption of any new treatment has to be vindicated by a demonstration of benefits that outweigh a possible clinically insignificant reduction in the reference treatment efficacy. Statistical methods have been developed to analyze data collected from noninferiority trials. However, these methods focus on cases with only one reference treatment. In this paper, we provide the statistical inferential procedures for situations with multiple reference treatments. The computation of the corresponding critical values for simultaneous testings of noninferiority of several new treatments to multiple reference treatments in the presence of a placebo is provided. Furthermore, for a prespecified level of test power, a technique to determine the optimal sample size before the onset of a noninferiority trial is derived. A clinical example is given to illustrate our proposed procedure.